A Content Analysis of Character Education Values in the English Students’ Textbooks for Senior High School in Indonesia - Rutela Renette; Safnil Safnil; Wisma Yunita (Yayasan Karinosseff Muda Indonesia, 2021)
The aim of this research is to find out a content analysis of character values in the English students’ textbooks for senior high school 10th grade, 11th grade and 12th grade and the dominant differences of character from all the books. This research employed qualitative method by using content analysis. For this research mainly character values in the textbooks was carried out. The data in this research were all passages that taken from the three English sudents’ textbooks for senior high school. This research used observation check list as the instruments to evaluate coursebooks in an effective and practical way. The researcher has analyzed the data based character values found on the three books. And all of the dominants character values that the researcher were found.